Cauliflower Leave, an Agricultural Waste Biomass Adsorbent, and Its Application for the Removal of MB Dye from Aqueous Solution: Equilibrium, Kinetics, and Thermodynamic Studies - Seraj Anwar Ansari; Fauzia Khan; Anees Ahmad (International Journal of Analytical Chemistry)
Cauliflower leaf powder (CLP), a biosorbent prepared from seasonal agricultural crop waste material, has been employed as a prospective adsorbent for the removal of a basic dye, methylene blue (MB) from aqueous solution by the batch adsorption method under varying conditions, namely, initial dye concentration, adsorbent dose, solution pH, and temperature. Characterization of the material by FTIR and SEM indicates the presence of functional groups and rough coarse surface suitable for the adsorption of methylene blue over it. Efforts were made to fit the isotherm data using Langmuir, Freundlich, and Temkin equation. The experimental data were best described by Freundlich isotherm model, with an adsorption capacity of 149.22 mg/g at room temperature. To evaluate the rate of methylene blue adsorption onto CLP, pseudo-first-order, pseudo-second-order, and intraparticle diffusion models were employed. The experimental data were best described by the pseudo-second-order kinetic model. Evaluation of thermodynamic parameters such as changes in enthalpy, entropy, and Gibbs’ free energy showed the feasible, spontaneous, and exothermic nature of the adsorption process. On the basis of experimental results obtained, it may be concluded that the CLP prepared from agricultural waste has considerable potential as low-cost adsorbent in wastewater treatment for the removal of basic dye, MB.